Pengembangan Media Manipulatif Papan Abce Pada Materi Luas Permukaan Bangun Ruang Sisi Datar - 'Aniqoh, Lazatin; Qohar, Abd; M. Husen Al Farisy (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
Junior high school students often struggle to understand mathematical concepts. Observations of classroom learning indicate that many students find it difficult to grasp mathematical ideas when there is no tangible representation of those concepts. One such challenge lies in understanding the surface area of three-dimensional geometric shapes with flat faces. Students’ academic performance is also influenced by their interest in the learning process and the tools used. This study aims to develop a manipulative learning media called the